Surgical outcomes of gastro‐entero‐pancreatic neuroendocrine tumors G3 versus neuroendocrine carcinoma. Issue 4 (26th May 2022) - Li, Mu‐Xing; Lopez‐Aguiar, Alexandra G.; Poultsides, George; Rocha, Flavio; Weber, Sharon; Fields, Ryan; Idrees, Kamran; Cho, Cliff; Maithel, Shishir K.; Zhang, Xu‐Feng; Pawlik, Timothy M.
Abstract: Background: To define surgical outcomes of patients with high‐grade gastro‐entero‐pancreatic neuroendocrine neoplasm grade G3 (GEP‐NEN G3). Methods: Patients who underwent surgical resection between 2000 and 2016 were identified. The overall survival (OS) and recurrence‐free survival (RFS) of patients with gastro‐entero‐pancreatic neuroendocrine tumors grade G3 (GEP‐NET G3) versus neuroendocrine carcinoma (NEC) were evaluated. Results: Fifty‐one out of 2182 (2.3%) patients who underwent surgical resection were diagnosed as GEP‐NEN G3. The pancreas was the most common primary site ( n = 3772.5%). A majority of patients had lymph node metastasis ( n = 3262.7%); one in three ( n = 1631.4%) had distant metastasis. The median OS and RFS of the entire cohort were 56.4 and 34.5 months, respectively. Perineural invasion was a strong prognostic factor associate with OS after surgical resection. Patients with NEC had a worse survival outcome versus patients with NET G3 (median OS: 33.1 months vs. not attained, p = 0.088). In contrast, among patients who underwent curative‐intent resection, patients with NEC had comparable RFS versus patients with NET G3 (median RFS: 35.6 vs. 33.9 months, p = 0.774). Conclusions: Surgical resection provided acceptable short‐ and long‐outcomes for well‐selected patients with resectable GEP‐NEN G3. NEC was associated with a worse OS versus NET G3.